Foetal cardiac function in third trimester pregnancies with reduced fetal movements. (2nd January 2022) - Saglam, Aylin; Derwig, Iris; Gul, Murat; Kasap, Burcu; Yilmaz, Nuh; Sezik, Mekin; Celik, Onder; Tiryaki, Sibel; Özcil, Mustafa Doğan; Sipahioğlu, Haydar; İnci, Sinan; Demircan, Fadime
Abstract: The objective of our study was to investigate the possible relationship between poor perinatal outcome and foetal cardiac functions in pregnant women with reduced foetal movements (RFM). This cross-sectional study included 126 pregnant women with normal foetal movements (Group 1, Controls) and 42 pregnant women over 32 weeks gestation with RFM (Group 2). Group 2 was further divided into two subgroups according to their perinatal outcome: normal perinatal outcome (Group 2a) and poor perinatal outcome (Group 2b). Cardiotocography, the E/A ratio in both atrioventricular valves, myocardial performance index (MPI) and foetal tricuspid annular plane systolic excursion (f-TAPSE) were evaluated. Foetuses with poor perinatal outcome had a higher MPI ( p  = .003), higher tricuspid and mitral E/A ( p  < .001), and lower f-TAPSE values ( p  < .001). In regression analysis, f-TAPSE was the only parameter ( p  = .04) independently associated with poor perinatal outcome. İn conclusion, examining f-TAPSE may predict adverse perinatal outcome in pregnancies with RFM. IMPACT STATEMENT: What is already known on this subject? Reduced foetal movement (RFM) is associated with adverse pregnancy outcome. Cardiotocography, amniotic fluid assessment, estimated birthweight, foetal Doppler and formal foetal movement count (kick chart) are generally used in the clinical assessment of pregnancies with reduced foetal movements. These tests, we currently use to assess foetal wellbeing in women with reduced foetal movements, have limited sensitivity in predicting foetal compromise. What do the results of this study add? Foetal cardiac Doppler may potentially be used as an important adjunct to the conventional management of women with a perception of reduced foetal movements. What are the implications of these findings for clinical practice and/or further research? Foetal echocardiographic evaluation, such as f-TAPSE, may influence clinical practice by enabling improved risk stratification for poor perinatal outcome, thus allowing more timely definitive intervention. This could help to decrease the rate of stillbirth related to reduced foetal movements. The few established echocardiographically derived parameters, which can asses global right ventricle function, are not always easy to obtain, however, f-TAPSE is easily obtainable using ultrasound and it appears to be a clinically useful echocardiographic measurement of right ventricular function.